The Landscape of IgA Nephropathy Treatment Strategy: A Pharmacological Overview - Vincenzo Di Leo; Francesca Annese; Federica Papadia; Iris Cara; Marica Giliberti; Fabio Sallustio; Loreto Gesualdo (MDPI AG, 2023)
IgA Nephropathy (IgAN) is the most common form of primary glomerulonephritis and is one of the most common causes of end-stage kidney disease (ESKD) worldwide. The immunopathogenic mechanism underlying IgAN is poorly identified. Currently, the mainstay treatment of IgAN is centered on the optimization of blood pressure and a reduction in proteinuria, using an angiotensin-converting enzyme inhibitor (ACEi) and angiotensin receptor blockers (ARBs). According to KDIGO, patients who persistently remain at a high risk of progressive ESKD, despite maximal supportive care, are candidates for glucocorticoid therapy. Recent discoveries regarding the pathogenesis of this disease have led to the testing of new therapeutic drugs targeting, in particular, the excessive mucosal immune reaction and the resulting systemic response as well as the complement activation and the following kidney damage and fibrosis. In this review, we examine the various therapeutic approaches to this intriguing disease.